PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN FISIK DALAM RUMAH TANGGA ( Studi P2TP2A Provinsi Sumatra Utara ) - Maria Ferba Editya S, SH, MH (Journal Recht (JR), 2022)
Violence against women and children is a violation of human rights. The integrated services centre of the women and children empowerment (Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak/P2TP2A) is an integrated activity founded Ministry of women empowerment and child protection and provide services for the Indonesian people, mainly women and children victims of violence acts. The purpose of this research is to know the service of process in P2TP2A given to women victims of domestic violence and P2TP2A efforts in tackling domestic violence. The research method used the juridical sociological. data collection is done by observation, interview and documentation as well as literature-related literature. Researchers took samples from Sumatera Utara P2TP2A because P2TP2A is a pilot project of P2TP2A in other districts.Then analyzed in descriptive qualitative.From the above research it can be concluded that the role of the integrated services centrethe empowerment of women and children (P2TP2A) in addressing domestic violence is very effective and in accordance with the mandated in the Act No. 23 years 2004 on the Elimination of Domestic Violence.